Pengaruh Penggunaan ProFormA Question Pada LMS Onelearn Dengan Implementasi PJBL Terhadap Peningkatan Kompetensi Kognitif Siswa - Firdiawati Firdiawati; Martini Dwi Endah Susanti (CV. SINAR HOWUHOWU, 2026)
The learning process of Structured Programming at SMK Krian 1 Sidoarjo is still dominated by teachers, while the use of the Moodle Learning Management System (LMS) is not optimal because it is still in the trial stage and has not been adjusted to the needs of the subjects. This condition causes active student involvement and cognitive competency development to not be maximized. This study aims to analyze the effect of the use of ProFormA Question on the OneLearn LMS with the implementation of Project Based Learning (PjBL) on improving students' cognitive competence. The study uses a quantitative approach with a One Group Pretest-Posttest design. The research subjects consisted of 35 students in class X RPL 1 SMK Krian 1 Sidoarjo. Data were collected through pretest and posttest tests, then analyzed using the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank test, and the N-Gain test. The results showed that there was an increase in students' cognitive competence after learning using ProFormA Question on the OneLearn LMS. The results of the Wilcoxon test showed a significant difference between the pretest and posttest scores (p < 0.001), while the results of the N-Gain test obtained an average value of 0.5659 which was included in the medium category. These results show that the use of ProFormA Question in the OneLearn LMS implemented with the Project Based Learning (PjBL) model has a positive effect on improving students' cognitive competence in Structured Programming subjects. Thus, the OneLearn LMS can be an effective alternative learning media in supporting programming learning in vocational schools.